The Relationship Between Extroversion and the Tendency to Anthropomorphize Robots: A Bayesian Analysis - Kaplan, Alexandra D.; Sanders, Tracy; Hancock, Peter A. (Frontiers in Robotics and AI, 2019)
An individual’s personality affects how they view their peers as well as machine entities such as robots. This study examined the relationship between the personality trait of extroversion and the tendency to rate a robot as anthropomorphic in an experimental setting. To evaluate this relationship, 486 participants completed relevant personality inventories and then viewed videos and images of robots performing common jobs (i.e., warehouse technician, IED detection). The participants then rated these robots on an assessment instrument scaling anthropomorphism. We observed a significant positive relationship between participants’ self-rated extroversion and their tendency toward anthropomorphization of the robots. A Bayesian regression analysis was performed to show the strength of their degree of extroversion as a predictor of the tendency to anthropomorphize. We conclude that personality dimensions affect how an individual views the robot that they interact with. This mediation promises to affect acceptance of, and use of, robots by differing individuals.